OPTIMALISASI MANAJEMEN PROYEK UNTUK KEBERHASILAN PELAKSANAAN PROYEK PELEBARAN JALAN - Hapsari, Indri Barianti; Mudiyono, Rachmat; Niam, Moh Faiqun (UNISSULA Semarang, 2024)
Project management functions to oversee the process of implementing construction work from the start of the project until the end of the project. In this research, the strategy used is the project management optimization handling strategy which will dominantly influence the implementation of the Palir Kaliancar Road widening project for the 2022 Fiscal Year. The aim of this research is to find out the factors that cause delays in implementing the Palir Kaliancar road widening project not on time. using the SWOT method.To find out the SWOT indicators that most influence the success in implementing the Palir Kaliancar Road Widening project, Semarang City. This research uses the SWOT (Strengths, Weaknesses, Opportunities, Threats) method to systematically identify various factors to formulate dominant project management optimization in the implementation of the Palir Kaliancar Road Widening project for the 2022 Fiscal Year. By conducting literature studies and research surveys, data collection includes data primary and secondary data then continued data processing. In the results of the IFE and EFE analysis of the components of the Palir Kaliancar Road Widening construction project in Ngaliyan, Semarang City, a value of Strength 4.24 Weakness 4.22 Opportunity 4.34 Threat 4.14 was obtained. For IFAS, you get a value of 0.01 from the Strength value minus the Weakness value, while the EFAS value gets a value of 0.1 from the Opportunity value minus the Threat value.From these results, you can determine the coordinates in the SWOT matrix quadrants. So the results of this combination show the coordinates of the SWOT quadrant matrix which is located in quadrant I, namely the strategy between the strength factor component (S) and the opportunity factor component (O). So the strategy developed for the Palir Kaliancar Road Widening Project component in Ngaliyan, Semarang City, uses a Progressive Strategy.